The Prophet's Household Problems and The Solving Method in Hadith - Alven Putra (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The household of the Prophet is an example that needs to be imitated by every Moslem; how he always tried to be just and wise as a husband in dealing with daily domestic problems. This paper aims to look at the household problems faced by the Prophet Muhammad SAW and his method in solving these problems, by referring to the traditions of the Prophet SAW (hadith). This research is a descriptive-qualitative with reference to library resources, both in the form of the Prophet's sirah and hadiths, taken from primary hadith compilation, books, scientific journals and other relevant library sources. Domestic turmoil is common in every household, even with the Messenger of God, starting from the jealousy between wives, the prosecution of material rights, to the accusations of adultery that befell Sayyidah 'Aisyah and Mariah Al-Qibtiyyah. As any other husband, there were so many household problems faced by the Prophet, yet he managed to find the best solution based on the conditions and situations. To resolve these problems, the Prophet confronted them with the method of smiling, teasing, reminding, and being patient, but also firm and did not hesitate to separate his wife for a while.